SEJARAH TOKOH PEMIKIR PADA MASA PERIODE PERTAMA DAN KEDUA - Maryam Batubara; Cahya Amelia; Cut Anggraini; Muhammad Arisandi Junjungan (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Islamic Economic Thought began when Muhammad SAW was sent as an Apostle. The object of study in Islamic economic thought is not only the teachings of the Qur'an and Sunnah, but Islamic scientists study Islamic economics in history or how to understand the teachings of the Qur'an and Sunnah regarding economics. After the development of Islamic economic thought after Rasulullah SAW and Khulafaurrasyidin, developments emerged in the Middle Ages which were divided into 3 periods based on the names of the lives of these Islamic economic figures. Namely Islamic Economics in the first period, second period and third period. This method study uses several book and journal references to strengthen this research to obtain credible data. The history of thought in the first period refers to the Al-Qur'an and Hadith in exploring the concepts of maslahah and mafsadah related to economics. History in the second period was a time when economic thinking was based on increasing corruption and moral decay, expanding the gap between rich and poor.